Evaluating admission procedures for teacher education in Finland - Kaasila, Raimo; Hannula, Markku S.; Laine, Anu; Pehkonen, Erkki (Teaching Mathematics and Computer Science, 2008)
In Finland the number of applicants for elementary teacher education is many times greater than the number of accepted persons. In this article we focus on the significance of the entrance examination procedures at three Finnish universities. Our findings imply that the differing admission procedures at the institutions yielded different student profiles. The test component "mathematics-science" used on the entrance examination in Turku was found to be a significant separating factor, but also the applicants’ mathematics achievement in upper secondary school seems to be an applicable criterion for developing admission procedures.